DOMESTIC AND FORIGN FACTORS FOR STOCK PRICES IN INDONESIA - Rahajeng Cahyaning Putri Cipto; Akhsyim Afandi (Economic Journal of Emerging Markets, 2010)
Indonesia has been developing various sectors of its economy, and so it needs a huge amount of capital. Therefore, it has been putting a lot of efforts to develop its capital market. This paper analyzes the impacts of domestic and foreign factors on Indonesia stock price. Some considered domestic factors are interest rates, production index, and foreign exchange rates. Various considered foreign factors are Singapore and US stock prices. The paper uses Vector Error Correction Mechanism model to analyze the data. The estimation results suggest that all variables significantly influence Indonesia stock price, with Singapore stock price as the dominant factors.Keywords: Stock price, interest rates, exchange rates, production indexJEL classification numbers: G12, G15